Pengaruh Jenis Pupuk dan Mulsa Terhadap Tingkat Infestasi Hama pada Capsicum annuum - Don Kadja; Petronella Nenotek (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
The purpose of this study was to determine the effect silver plastic mulch combined with the application of bokashi fertilizer on chili plants. This study was carried out from August to November 2021. This study had 18 treatment units consisting of: A1: planting media fertilized with bokashi and covered with silver plastic mulch, A2: growing media fertilized with bokashi and without mulch, B1: growing media fertilized with Urea, SP36, KCL and covered with silver plastic mulch, B2: growing media fertilized with Urea, SP36, KCL without mulch, C1: planting media fertilized with Urea, SP36, KCL + bokashi and covered with silver plastic mulch, C2: planting media was fertilized with bokashi + Urea, SP36, KCL, without mulch. The results showed that the use of mulch and bokashi gave better results (least pest infestation of all treatment), but statistically there was no significant difference between the treatments on the observed variables.